Sensitization of TiO2 by dyes: A way to extend the range of photocatalytic activity of TiO2 to the visible region - Litter, Marta Irene; San Roman, Enrique Arnoldo; Grela, Maria Alejandra; Meichtry, Jorge Martin; Rodriguez, Hernan Bernardo (Wiley VCH Verlag, 2018)
Fil: Litter, Marta Irene. Comisión Nacional de Energía Atómica; Argentina. Universidad Nacional de San Martín. Instituto de Investigación e Ingeniería Ambiental. - Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Investigación e Ingeniería Ambiental; Argentina